Secret Ingredient / Beezuel Sulihan ... [et al.] - Sulihan, Beezuel; Lansu, Kennedy; Alias, Norazwah Nieza; Mohd Taip, Nurfatin Athirah; Hadi, Siti Nabilah (2013)
The name of our company is Secret Ingredient. Secret ingredient is a business that provides foods and drinks. Our main menu is cold dessert. The nature of our business is partnership. Our main cafe is located at Alamesra, Kota Kinabalu. Secret Ingredient, Lorong Plaza Permai 6, Lot85, J - 1 , 88400, Kota Kinabalu, Sabah. We aspect to start up our business on 14th February 2014. The future prospects of our business are people around Malaysia and at the same time aiming the international customer. This is because, not many cafe around Malaysia provide this menu and we aspect this business have a high potential to expand.